PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP SMP MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2016/2017 - Arin Septiana; Ningrum Ningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The learning process shouldbe supported by the interaction between students and teachers. Students who have no interest at the time of study should be given the solution, because it will impacts for low student in learning outcomes. One of the solutions is to improve less interesting learning processthat is by applying cooperative learning model take and give type. The problem formulation in this research “is there any influence of using cooperative learning model take and give type to wards the students’ learning outcomes in Social Science at VIII Grade of SMP Muhammadiyah 1 Metro in even semester of 2016/2017?” The purpose of this study is to determine the effect of cooperative learning take and give typetowards the students’ learning outcomes in Integrated Social Science at VIII Grade of SMP Muhammadiyah 1 Metro in even semester of 2016/2017?. Data collection techniques used in this study are observation, interview, documentation and test. Hypothesis in this study is “There is a positive influence of usingcooperative learning model take and give type to wards the students’ learning outcomes in Integrated Social Science at VIII Grade of SMP Muhammadiyah 1 Metro in even semester of 2016/2017?. Population in this study is all students of VIII Grade, and the determination of the sample by using cluster random sampling selected to be the sample is class VIIIB as an experimental class and class VIIIC as a control class. Next, see from simple linear regression calculation can be known that the hypohtesis is received because thit> ttab can be seen at the real level 5% thet is2,6589 > 1,70 and on a real level 1% thet is 2,6589 > 2,47. Therefore, there is a positive influence of usingcooperative learning model take and give type to wards the students’ learning outcomes in Integrated Social Science at VIII Grade of SMP Muhammadiyah 1 Metro in even semester of 2016/2017.Keywords: Cooperative Learning Model Take And Give Type And Integrated Social Scienceof Learning Outcomes